Effects Of Pandemic and War on Youth Migration: A Quantitative Study in Poland and Portugal - Grazyna KOWALEWSKA; Nelson DUARTE; Izabela ZABIELSKA; Marek PIOTROWSKI (Communications of International Proceedings, 2023)
The article is a continuation of original international research conducted in 2017 and 2020 among young people, management students in Poland and Portugal. Both countries are characterized by mass emigration among young, educated people. The most important reasons for leaving the country are economic reasons. However, it seems interesting to examine other factors that may influence their migration decisions. Non-economic factors seem to be particularly important, related to the emergence of two crises: the pandemic and the war. The aim of the article is to determine the impact of the Covid-19 pandemic, the emergence of the Covid-19 vaccine and the Russian-Ukrainian war on respondents' willingness to migrate. In the 2022 197 students (93 from Poland and 104 from Portugal) participated in the survey. To verify the hypotheses, the following were used, among others: binomial logistic regression model. The study found that the fear of contracting Covid-19 has a negative impact and the arrival of a Covid-19 vaccine has a positive impact on young people's willingness to migrate. Perceptions of war vary depending on distance from the conflict. War as a migration barrier is twice as important a factor influencing migration decisions for Poles than for the Portuguese. Poles also see the possibility of moving the war from Ukrainian territory to their country
Keywords: migration; students; COVID-19; war.